Utopias de Brasília no cinema : o desvio contra a arquitetura e a história - Tatiana Hora Alves de Lima (2019)
Brasilia was built up with the utopic pledge of refounding the country. This city inspired the realisation of a vast amount of movies. Among them, on one hand, propaganda films created by New Town Development Company(Novacap), since the construction of the city, which exalted the founding myths, the “50 years in 5”, the leadership of Juscelino Kubitschek and the indefatigable workers who built the new capital. On the other hand, several films deviated from the utopias of Brasilia. We start from the concept of deviation created by Guy Debord, in collaboration with the situationists, and attempt to enlarge it, in order to address the deviating gestures in the films which compose the corpus of this research. Our purpose is to analyse how the films Brasília segundo Friedman (1979), by Vladimir Carvalho, Fala Brasília (1966), by Nelson Pereira dos Santos, Brasília, contradições de uma cidade nova (1967), by Joaquim Pedro de Andrade (opposing Brasília, planejamento urbano (1964), by Fernando Coni Campos), Conterrâneos velhos de guerra (1991), by Vladimir Carvalho, A cidade é uma só? (2011), Branco sai, preto fica (2014), and Era uma vez Brasília (2017), the last three directed by Adirley Queirós, deflect the senses proposed by the official architecture and the official history, through the articulation among bodies, time and space, following the opposite direction of the historical time underpinned in the concept of progress.